2017
DOI: 10.1016/j.jor.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Bone remodelling around the Metha ® short stem implant – Clinical and dual-energy x-ray absorptiometry (DXA) results

Abstract: The concept of metaphyseal ingrowth was confirmed, but distal bony reactions need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…Densitometry showed an increase in bone mineral density in the proximal and distal lateral zones around the Metha stem and a decrease in bone mineral density in the proximal medial and central lateral zones around the tested implant. The reported observation confirms the process of remodelling and healing of the stem into the mataphyseal region of the proximal femoral bone 37 .…”
Section: Discussionsupporting
confidence: 85%
“…Densitometry showed an increase in bone mineral density in the proximal and distal lateral zones around the Metha stem and a decrease in bone mineral density in the proximal medial and central lateral zones around the tested implant. The reported observation confirms the process of remodelling and healing of the stem into the mataphyseal region of the proximal femoral bone 37 .…”
Section: Discussionsupporting
confidence: 85%
“…Consequently, short hip stems and even neck stems have become the latest concepts. These stems help preserve the femoral neck, keep the anatomical elasticity of the femur and introduce the forces in the upper part of the femur [18,51,[58][59][60][61][62][63][64]. And studies evaluated periprosthetic bone remodeling with DEXA showed a more balanced remodeling and favorable load transfer of the short stem in comparison to standard hip stem [16,51,[60][61][62][63][64][65].…”
Section: Implant-related Factorsmentioning
confidence: 99%
“…Some authors investigated the bone remodelling characteristics of the femur after THA with a METHA stem by using DEXA assessment and adapting Gruen zones (R1 to R7) to the short stem design. 89 92 In all studies including 176 hips with at least one year of follow-up, the bone mineral density (BMD) significantly increased in the lateral regions (R2 and R3) and significantly decreased in the proximal regions (R1 and R7). On the other hand, changes in distal (R4), distal-medial (zone 5) and lesser trochanter (R6) regions were less relevant and reliable across the analysed studies.…”
Section: Stem Features and Outcomesmentioning
confidence: 99%